A visualization approach to prioritizing insurance claims from complex, multi-PRP Superfund sites. Issue 3 (3rd July 2019) - Ludvigsen, Phillip; Green, Scott; Heltzer, Josh; Lee, John
Abstract: The severity of environmental insurance claims related to large multi-PRP Superfund sites has grown over the last 30 years. When an insured files a Superfund-related claim, allocated costs to the insured are typically unknown. Assessing the insured's likely share of future cleanup costs is challenging. This article proposes a simple approach that allows claims professionals to visualize where their insured stands relative to other PRPs' potential allocation of cleanup costs. The resulting color-coded "heat map" allows claims professionals to easily assess and prioritize potential insured losses. It also provides a starting point for settlement negotiations, thus reducing frictional costs.